Pleomorphic adenoma of the soft palate: Myoepithelial cell predominant - Deepak Daryani; R Gopakumar; Vidya Ajila (Wolters Kluwer Medknow Publications, 2011)
The pleomorphic adenoma is the most common salivary gland tumor. A remarkable morphological diversity can exist from one tumor to the next. We present here a case of pleomorphic adenoma of minor salivary glands of the soft palate which had predominantly myoepithelial cells with minimal stroma, ductal cells, or tubular elements.